Methods of Involving Children who are Not Included in Pre-School Education Organizations to Private Pre-School Education Organizations - Ra’no Turapova Barat's Qizi; Baxriddinova Fazilat (Genius Journals, 2023)
In this article, you can get enough information about the methods of attracting children who are not included in the preschool education organization to the private preschool education organization.
Keywords: Preschool education organization; children; educator; parents